PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA PENGRAJIN TENUN BINAAN DINAS KOPERASI UKM DAN TENAGA KERJA KABUPATEN WAKATOBI - Arif Rahman Syah; Endro Sukotjo; Sudirman Zaid; Salma Saleh; Valentinus Amstrong TN; Riski Amalia Madi (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
The purpose of this study was to examine the effect of product quality, price and promotion on purchasing decisions of woven fabrics, influence of product quality on purchasing decisions of woven fabrics, influence of price on purchasing decisions of woven fabrics and the influence of promotions on purchasing decisions of woven fabrics. The object of this research is the Department of Cooperatives, Small and Medium Enterprises and Manpower of Wakatobi Regency. The approach used in this research is a quantitative approach (mainstream approach). The sample/respondent used in this study were 100 respondents. The analytical tool used is Multiple Regression Analysis. Data collection methods in this study used a questionnaire and data analysis tools using software SPSSThe results of this study can be concluded that product quality, price and promotion together have a strong and significant influence in improving the purchasing decision of Wakatobi woven fabrics, product quality significantly affects the improvement of fabric purchasing decisions, price significantly affects the increase of woven fabric purchasing decisions and Promotion significantly affects the increase in purchasing decisions for Wakatobi woven fabrics.